Determining the Priority Factors that Influence the Intention to Invest in Cryptocurrencies using Fuzzy Analytical Hierarchy Process - Raymond Wahyudi; Nanik Linawati; Farrell Ionwyn Eduardo (Jurnal Computech & Bisnis (e-journal), 2024)
Cryptocurrency investment is a phenomenon that has gained popularity among Indonesian youth. However, the factors that influence their intention to invest in this digital asset class are not well understood. This study aims to identify and evaluate these factors using the Fuzzy Analytical Hierarchy Process (FAHP) method, which can handle uncertainty and ambiguity in decision making. The study applies the Unified Theory of Acceptance and Use of Technology (UTAUT) model as the theoretical framework, and considers six factors: social influence, financial literacy, facilitating condition, performance expectancy, effort expectancy, and hedonic motivation. The results show that social influence, financial literacy, and facilitating condition are the most important factors, while hedonic motivation is the least important. The study also ranks the sub-criteria within each factor according to their relative importance. The findings provide valuable insights for policymakers, investors, and educators in the field of cryptocurrency and blockchain technology.